Education of Children Perspective Hadith - Pratiwi, Yulia Sukma Rahma (Atthulab: Islamic Religion Teaching and Learning Journal, 2023)
This study aims to discuss educating children from the hadith perspective. This research is a qualitative type that applies literature study using a thematic study approach. The results and discussion of this study include methods that can be used in educating children from a hadith perspective. This study concludes that the method of educating children is very important to apply, especially with today's conditions. The application of methods in the educational process must really be considered, so that it can affect effectively every child's development. So that children can grow and develop properly. The existence of the right method applied in educating children can make it the foundation to support their success in the future.